A reflection of local supplier development towards sustainable social supply chain - Munira, Halili; Fernando, Yudi (KnE Social Sciences, 2019)
In today’s business environment, supplier management is increasingly inclined to complexity and uncertainty due to rapid technological changes and globalization. The objective of this study is to review the necessary important of local supplier development towards sustainable social supply chain. Supplier management must be handled systematically, and maintaining a good relationship between manufacturer and supplier is vital. Therefore, it is critical for the supplier in making a well-informed decision. As an alternative, firms should consider developing a local supplier in making sure the availability of fast and reliable supplies to meet global requirement. The criticality is due to supplier selection contributes to overall supply chain performance. This study concludes that developing a local supplier will reduce the increased pressure to develop a direct economic relationship with local communities.